(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2021)
The study proposes an analysis of the development in Italy of mosaics decorated with labyrinths and the subject of city walls. First, the autonomous statement of the subjects is defined. Subsequently, the paper proposes a revision of the traditional interpretation of the two associated motifs, in light in particular of the social and cultural context of the Romanization of the whole Italic territory.